Examining the Role of Multiplayer Online Games in Enhancing Communicative Competence: Insights from Kuwaiti Students - Satheesh, Pratheeksha; Daimari, Kamathenu (Journal of Research in Vocational Education, 2026)
This research investigates how multiplayer online games MMORPGs affect the communicative competence of Kuwaiti students learning English as a foreign language. The study identifies how MMORPGs offer an immersive environment for students to enhance their language skills, focusing on collaboration and interaction with native speakers. The research also highlights the impact of motivation and the communities of practice within the game, suggesting the potential of MMORPGs to boost second language acquisition by reducing anxiety and fostering engagement.